2015
DOI: 10.1007/s11019-015-9631-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding empathy: why phenomenology and hermeneutics can help medical education and practice

Abstract: This article offers a critique and reformulation of the concept of empathy as it is currently used in the context of medicine and medical care. My argument is three pronged. First, that the instrumentalised notion of empathy that has been common within medicine erases the term's rich epistemological history as a special form of understanding, even a vehicle of social inquiry, and has instead substituted an account unsustainably structured according to the polarisations of modernity (subject/object, active/pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
(99 reference statements)
0
30
0
5
Order By: Relevance
“…Following Reidar Pedersen, Rebecca Garden and others, we argue that an underlying and problematic discursive structure unifies these apparently disparate and oppositional accounts: they are all structured by the polarised dichotomies between subject and object, knower and known, mind and body, active and passive, science and society, culture and nature, (and masculine and feminine) that underpin modernity4 7 Thus, all these accounts reproduce the ideals of objectivity and neutrality in medicine, such that the subjectivity of the doctor , who is supposed to be both objective and neutral, is constantly elided, while the subjectivity of the patient is brought into view 14. Similarly, all these accounts construct empathic knowing as oppositional to, and hence needing to be kept in check by, the technical knowledge of medicine.…”
Section: Empathy and The Problems Of Modernitymentioning
confidence: 83%
See 3 more Smart Citations
“…Following Reidar Pedersen, Rebecca Garden and others, we argue that an underlying and problematic discursive structure unifies these apparently disparate and oppositional accounts: they are all structured by the polarised dichotomies between subject and object, knower and known, mind and body, active and passive, science and society, culture and nature, (and masculine and feminine) that underpin modernity4 7 Thus, all these accounts reproduce the ideals of objectivity and neutrality in medicine, such that the subjectivity of the doctor , who is supposed to be both objective and neutral, is constantly elided, while the subjectivity of the patient is brought into view 14. Similarly, all these accounts construct empathic knowing as oppositional to, and hence needing to be kept in check by, the technical knowledge of medicine.…”
Section: Empathy and The Problems Of Modernitymentioning
confidence: 83%
“…A critical shift that many of these works have made is to cease thinking of empathy as something we have and to being thinking of it as something we do. Thus, several recent psychologically based models of empathy incorporate affective, cognitive and behavioural elements, and draw out—literally— processes for how empathy occurs, mapping the pathways that link these elements 4 19 20. Others have suggested that we understand empathy performatively , as something we enact , in ways very like—or the same as—emotional labour 19.…”
Section: Empathy and The Problems Of Modernitymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that physicians who can empathize with their patients provide better care than those who are unable to empathize (Eikeland et al 2014;Derksen et al 2013;Di Blasi and Kleijnen 2003;Halpern 2001;Hojat et al 2011Hojat et al , 2013Hooker 2015;Pedersen 2008;Roter et al 1998). Empathy greatly enhances the physician-patient interaction, allowing for the physician to better understand the patient's experiences, and therefore better understand how the patient should be treated.…”
Section: The Benefits Of Empathy For Patients and Physiciansmentioning
confidence: 99%